2021
DOI: 10.3332/ecancer.2021.1178
|View full text |Cite
|
Sign up to set email alerts
|

Pathological complete response to neoadjuvant chemotherapy, but not the addition of carboplatin, is associated with improved survival in Chilean triple negative breast cancer patients: a report of real world data

Abstract: Background: Breast cancer (BC) is the leading cause of cancer death for Chilean women. About 11% of cases are triple-negative (TN) BC. These are characterised by poor prognosis, higher risk of early recurrence and visceral dissemination versus other BC subtypes. Current standard treatment for early-stage non-metastatic TNBC patients consists of neoadjuvant chemotherapy (NACT) followed by surgery and radiotherapy. Pathological complete response (pCR) to NACT is associated with an increase in survival rates. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…An apparent difference in the OS following neoadjuvant treatment between TNBC patients with and without attaining pCR was shown in this study, with an aHR of 0.27 (CI: 0.15-0.51) for favoring the pCR population. Unfortunately, an increased chance of achieving pCR (adjusted OR: 2.60, CI: 1.59-4.26) following platinum-based therapy did not translate to a long-term survival benefit among both the pCR and non-pCR populations, despite great effort being made in this study to address the methodology concerns that have been raised in previous real-world studies (14)(15)(16)(17). That is, we adjusted for potential confounding effects attributable to patient baseline conditions using multivariate regression models and stratified the analyses by patients' pCR status to generate precise study estimates for the pCR and non-pCR populations separately.…”
Section: Effect Of Platinum On Pcr and Os Among Patients With Tnbcmentioning
confidence: 80%
See 2 more Smart Citations
“…An apparent difference in the OS following neoadjuvant treatment between TNBC patients with and without attaining pCR was shown in this study, with an aHR of 0.27 (CI: 0.15-0.51) for favoring the pCR population. Unfortunately, an increased chance of achieving pCR (adjusted OR: 2.60, CI: 1.59-4.26) following platinum-based therapy did not translate to a long-term survival benefit among both the pCR and non-pCR populations, despite great effort being made in this study to address the methodology concerns that have been raised in previous real-world studies (14)(15)(16)(17). That is, we adjusted for potential confounding effects attributable to patient baseline conditions using multivariate regression models and stratified the analyses by patients' pCR status to generate precise study estimates for the pCR and non-pCR populations separately.…”
Section: Effect Of Platinum On Pcr and Os Among Patients With Tnbcmentioning
confidence: 80%
“…Considering that the platinum-associated benefit for pCR did not translate to better survival outcomes in both trial ( 11 , 12 , 28 ) and real-world TNBC populations ( 15 17 ), novel agents such as immunotherapy should be considered in the neoadjuvant setting for this population ( 29 , 30 ). Specifically, the KEYNOTE-522 trial as an example demonstrated that the addition of pembrolizumab, an immune checkpoint inhibitor targeting programmed death 1, to conventional chemotherapy including carboplatin not only increased the pCR rate but also provided a longer event-free survival than the use of chemotherapy alone ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, the first report concerning real-world data on the Chilean population covered that females of TNBC in the phase of I–III received NAT of contained platinum. The result showed that the PCR rate was associated with extended overall survival, invasiveness, and disease-free survival, however whether the Cb exists or not was irrelevant to variability in survival indicators [ 37 ]. Similarly, other 2 studies suggest that whether patients of TNBC use platinum agents or not was related to PCR rate, which can induce the incidence of adverse reactions in the blood system increased markedly, such as febrile neutropenia [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer (BC) is the most common malignant tumor in women. One of the greatest challenges for clinicians remains to control BC invasiveness and dissemination in order to improve patient survival [ 1 , 2 ]. Indeed, although the treatment options of BC with surgery, chemotherapy, aromatase inhibitors, hormone receptor modulators, and anti-Human Epidermal Growth Factor Receptor 2 (HER2)-Therapy [ 3 , 4 , 5 ] have developed tremendously in recent years, consistently high mortality rates due to tumor metastasis remain [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%